2020
DOI: 10.1111/adb.12873
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant reward prediction errors in young adult at‐risk alcohol users

Abstract: Previous studies suggest that individuals with substance use disorder have abnormally large responses to unexpected outcomes (reward prediction errors [RPEs]). However, there is much less information on RPE in individuals at risk of alcohol misuse, prior to neurobiological adaptations that might result from sustained alcohol use. Here, participants (mean age 23.77 years, range 18-32 years) performed the electrophysiological monetary incentive delay task. This task involved responding to a target stimulus follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 60 publications
(170 reference statements)
1
14
0
Order By: Relevance
“…Therefore, the MID task may be considered a proxy to a true temporal‐difference learning task that engenders more reliable expectancies. Nonetheless, previous work has recommended the use of modulators in the MID task (Bjork et al., 2010; Oldham et al., 2018), and recent studies have found that prediction error was positively related to activation in the bilateral VS (Cao et al., 2019) and substance use problems in young adults (Cao et al., 2020) during the MID.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the MID task may be considered a proxy to a true temporal‐difference learning task that engenders more reliable expectancies. Nonetheless, previous work has recommended the use of modulators in the MID task (Bjork et al., 2010; Oldham et al., 2018), and recent studies have found that prediction error was positively related to activation in the bilateral VS (Cao et al., 2019) and substance use problems in young adults (Cao et al., 2020) during the MID.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional electrodes were located on the mastoids. EEG data were pre-processed using the EEGLAB toolbox 36 and the Fully Automated Statistical Thresholding for EEG Artifact Rejection (FASTER) plug-in, 37 as in Cao et al 11 The raw EEG data were band pass filtered from 0.1 to 95 Hz, and a 50-Hz notch filter was applied. The data were then average-referenced across all scalp electrodes.…”
Section: Eeg Data Acquisition and Pre-processingmentioning
confidence: 99%
“…During reward anticipation, however, fMRI studies have shown hypoactivation of the main areas of the reward circuit in AUD 3–5 although brain activity during this decision period in populations exhibiting risky drinking behaviours has not yet been investigated. The present study builds upon our prior EEG work, 11 providing a complete picture of both phases of reward processing, by evaluating the neural dynamics of reward anticipation in at‐risk drinkers. Here, we used an EEG version of the monetary incentive delay (eMID) task 11,14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations